Student’s Problem-Solving Skills in Thermodynamics at Dampelas 1 Senior High School - Nadia Rahmah; Darsikin Darsikin (Jurnal Ilmiah Pendidikan Fisika, 2021)
This study explores students' problem-solving skills in thermodynamics at Grade XI Science Senior High School 1 Dampelas. This research is a qualitative descriptive study.  The research subjects consisted of 6 students was conducted in a high school in Dampelas. The research instrument used was a test of student’s problem-solving skills on thermodynamic based on Polya's problem-solving. Respondents consist of various cognitive abilities (high, medium, and low). They were also willing to do an interview. This study indicated that students' problem-solving skills on thermodynamic materials based on Polya's problem-solving steps in the "problem understanding stage" indicator are in the moderate category. Similarly, the "planning stage" indicator is categorized in the moderate category, whereas the "implementation stage" indicator. The "revisiting stage" falls into the moderate medium category with an average percentage of 66.66 %. This research implies that it is hoped that the teacher can use the Polya stages in giving practice questions or homework to students to solve physics problems.